Improving Students’ Vocabulary Mastery by Using English Song at Grade VII SMP Muhammadiyah Sibabangun - Napitupulu, Maizar Nani; Huda, Rahmat; Rezeky Purba, Happy Sri (CV. Alfa Pustaka, 2025)
This study sought to improve students' vocabulary acquisition by using English lagugu. To collect data, the researcher conducted Classroom Action Research (PTK) consisting of four stages: planning, action implementation, observation, and reflection. The research subjects were the seventh-grade students of SMP Muhammadiyah Sibabangun, totaling 25 students. This research was carried out around two cycles, namely the first cycle consisted of two meetings and the second cycle consisted of one meeting. Data collection instruments used vocabulary tests and questionnaire sheets. Based on the vocabulary test, students' scores continued to increase in each test. The students were given four stages of tests namely: pre-test I, pre-test II, post-test I, and post-test II. The students' pre-test I score totaled 880 and the mean score was 35.2%. The pre-test II score totaled 1105 and a mean score of 43.8%, the post-test I score totaled 1985 and a mean score of 79.4%. And students' post-test II scores total score 2115 and mean score 84.6%.